Antibiotic resistance in Italian poultry meat production chain: a one-health perspective comparing antibiotic free and conventional systems from the farming to the slaughterhouse - Ferri, Gianluigi; Buonavoglia, Alessio; Farooq, Muhammad; Festino, Anna Rita; Ruffini, Fausto; Paludi, Domenico; Di Francesco, Cristina E.; Vergara, Alberto; Smoglica, Camilla (Frontiers in Food Science and Technology, 2023)
In this study a multidisciplinary approach was applied in order to determine the diffusion of resistant bacteria and selected antibiotic resistance genes in antibiotic-free and conventional broiler farms. Litter samples coming from the two farming types and surface sponges obtained from carcasses at slaughterhouse level were screened by end-point PCR targeting specific resistance for tetracycline, ampicillin, sulfonamide, aminoglycoside, carbapenem, nitrofurantoin, vancomycin, quinupristindalfopristin, lincomycin, linezolid, chloramphenicol molecules. Microbiological investigations were conducted from the carcasses to determine phenotypical and genetic resistance patterns from pathogenic and commensal Gram-negative and Gram-positive strains. At farm level, catA1, sul2, blaTEM and aadA2 genes were amplified in all samples, while from carcasses the most representative genes were sul2, blaTEM, along with the vatD, relative to quinupristin-dalfopristin resistance. Gramnegative isolates included Aeromonas, Salmonella, Proteus spp. and Escherichia coli, while the Gram-positive were represented by Enterococcus strains. Phenotypical and genetic analysis revealed multidrug resistance patterns in Salmonella, E. coli and Serratia isolates, followed by the Enterococcus species. The comparison between antibiotic-free and conventional farming systems showed some difference regarding the distribution of resistance genes at farm level but no significance was obtained comparing the phenotypical resistance profiles of bacterial strains from both groups of samples, suggesting a poor influence of farming model on the diffusion of antibiotic resistance in poultry meat production chain.